2023
DOI: 10.1515/geo-2022-0449
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the building of a weather information service for solar panel cleaning operations at Diass plant (Senegal, Western Sahel)

Abstract: The accumulation of dust on the surface of solar panels reduces the amount of sunlight reaching the solar cells and results in a decrease in panel performance. To avoid this loss of production and thus, to improve the performance capacity, solar panels must be cleaned frequently. The West African region is well known for its high solar energy potential. However, this potential can be reduced by the high occurrence of dust storms during the year. This article aims to provide a contribution to the construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Clauzel et al (2024) identified desert dust aerosol as a significant source of GHI forecast errors for the only two solar power plants in the Sahel region of Sococim (Senegal) and Zagtouli (Burkina Faso), particularly during the dry season. Dust aerosols are a key element in the West African climate and strongly influence solar farm production through their direct effect (aerosol-radiation interaction (ARI), Briant et al, 2017) and indirect effects (aerosolcloud interaction (ACI), Tuccella et al, 2019) on radiation, and also through their deposition on solar panels (fouling effect, Diop et al, 2020, Aidara et al, 2023. As mentioned by Kok et al (2021), the West African desert aerosol load is the highest in the world and occurs mainly during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Clauzel et al (2024) identified desert dust aerosol as a significant source of GHI forecast errors for the only two solar power plants in the Sahel region of Sococim (Senegal) and Zagtouli (Burkina Faso), particularly during the dry season. Dust aerosols are a key element in the West African climate and strongly influence solar farm production through their direct effect (aerosol-radiation interaction (ARI), Briant et al, 2017) and indirect effects (aerosolcloud interaction (ACI), Tuccella et al, 2019) on radiation, and also through their deposition on solar panels (fouling effect, Diop et al, 2020, Aidara et al, 2023. As mentioned by Kok et al (2021), the West African desert aerosol load is the highest in the world and occurs mainly during the dry season.…”
Section: Introductionmentioning
confidence: 99%